Integrative proteome analysis implicates aberrant RNA splicing in impaired developmental potential of aged mouse oocytes. Issue 10 (28th September 2021) - Li, Mingrui; Ren, Chao; Zhou, Shuai; He, Yuanlin; Guo, Yueshuai; Zhang, Hao; Liu, Lu; Cao, Qiqi; Wang, Congjing; Huang, Jie; Hu, Yue; Bai, Xue; et al.
Abstract: Aging has many effects on the female reproductive system, among which decreased oocyte quality and impaired embryo developmental potential are the most important factors affecting female fertility. However, the mechanisms underlying oocyte aging are not yet fully understood. Here, we selected normal reproductively aging female mice and constructed a protein expression profile of metaphase II (MII) oocytes from three age groups. A total of 187 differentially expressed (DE) proteins were identified, and bioinformatics analyses showed that these DE proteins were highly enriched in RNA splicing. Next, RNA‐seq was performed on 2‐cell embryos from these three age groups, and splicing analysis showed that a large number of splicing events and genes were discovered at this stage. Differentially spliced genes (DSGs) in the two reproductively aging groups versus the younger group were enriched in biological processes related to DNA damage repair/response. Binding motif analysis suggested that PUF60 might be one of the core splicing factors causing a decline in DNA repair capacity in the subsequent development of oocytes from reproductively aging mice, and changing the splicing pattern of its potential downstream DSG Cdk9 could partially mimic phenotypes in the reproductively aging groups. Taken together, our study suggested that the abnormal expression of splicing regulation proteins in aged MII oocytes would affect the splicing of nascent RNA after zygotic genome activation in 2‐cell embryos, leading to the production of abnormally spliced transcripts of some key genes associated with DNA damage repair/response, thus affecting the developmental potential of aged oocytes. Abstract : In this study, we constructed the dynamic proteomics of mouse MII oocytes during female aging. Analysis of differentially expressed proteins pointed out that a large number of splicing proteins were down‐regulated in aged mouse oocytes, suggested RNA splicing as a novel mechanism to regulate mouse oocyte aging. Dysregulation of key splicing factors, such as PUF60, relates to the impaired developmental potential of aged mouse oocytes.